Smart composite nanofiber mats with thermal management functionality - Nuray Kizildag (Nature Portfolio, 2021)
Abstract Nanofibers with thermal management ability are attracting great attention in both academia and industry due to the increasing interest in energy storage applications, thermal insulation, and thermal comfort. While electrospinning is basically a fiber formation technique, which uses electrostatic forces to draw ultrafine fibers from a wide variety of polymers, with the addition of phase change materials (PCMs) to the electrospinning solution it enables the production of shape stabilized phase change materials with thermal management functionality. In this study, polyacrylonitrile (PAN) nanofibers containing paraffinic PCMs were produced by electrospinning method and the composite nanofibers obtained were characterized in terms of their morphology, chemical structure, thermal properties, stability, thermal degradation behaviour and hydrophobicity. Besides, PCMs with different phase transition temperatures were added simultaneously into the nanofiber structure in order to investigate the tunability of the thermoregulation properties of the nanofibers. Uniform nanofibers with thermal management functionality were obtained. It could be possible to obtain composite nanofibers showing thermoregulation ability over a wider temperature range by simultaneous addition of PCMs with different melting points into the nanofiber structure. 50 wt% PCM could be added to PAN nanofiber structure wherein the resulting nanofiber exhibited 58.74 J g−1 of enthalpy storage during heating and 57.41 J g−1 of heat release during cooling. The composite nanofibers maintained their cylindrical fiber morphology, structure and composition after multiple heating–cooling cycles and retained their thermal management functionality. The contact angle measurements showed that the addition of PCMs imparted hydrophobicity to the nanofibers.